Why do people seek knowledge? Tracing factors that affect knowledge seeking intention - Veeravalli, Suchitra; Venkatraman, Vijayalakshmi; Hariharan, Manoj (VINE journal of information and knowledge management systems, 2020)
Purpose The purpose of this study is to understand factors that motivate an individual to seek knowledge on knowledge management systems. Specifically, the work seeks to clarify the impact of organizational practices on an individual’s intention to seek knowledge. The overarching theme is to broaden the current understanding of factors that impact individual knowledge seeking behavior and narrow down factors for which interventions can be developed. Design/methodology/approach In-depth interviews were conducted with the members of knowledge management (KM), human resources (HR) and learning and development teams of Robert Bosch Engineering and Business Solutions Private Limited (RBEI) to understand knowledge behaviors of employees. Subsequent to an exploratory analysis, the survey methodology was used to collect data from members of RBEI. A proposed theoretical model was then validated using partial least squares. Findings Empirical findings suggest that to motivate participation, organizational KM practices need to be geared towards promoting curiosity and engaging learners. Results indicate that overt recognition of knowledge seeking behaviors by HR could be counterproductive. Research limitations/implications This study was limited to an MNC engineering organization in one geographic location; one must be cautious when generalizing these results. Replicating this study in multiple organizations will help mitigate this limitation. Originality/value Little is known on the effect of KM and HR practices on knowledge seeking behaviors. This work addresses this gap and presents a comprehensive model.